Intellectual capital, digital transformation and firms’ financial performance: Evidence from ecological protection and environmental governance industry in China - Jian Yin; Jian Xu (PLoS ONE, 2025)
As the pace of enterprise digital transformation accelerates, intellectual capital (IC) has become a core driving force of gaining market competitive advantages and enhancing value creation capabilities. The paper aims to investigate the impact of IC and its components on financial performance of Chinese ecological protection and environmental governance companies during 2018–2021. In addition, the moderating effect of digital transformation between them is examined. IC is measured by the modified value added intellectual coefficient (MVAIC) model, and the measurement of digital transformation is based on text mining. The results suggest that IC can improve firm financial performance, especially during COVID-19. Physical capital, human capital (HC), and relational capital (RC) positively affect financial performance, while structural and innovation capitals have no significant impact. In addition, digital transformation strengthens the positive relationship between IC and its two elements (HC and RC) and financial performance. Heterogeneous analysis finds that the relationship between RC and innovation capital and financial performance is positive before COVID-19, and it is not significant during COVID-19. For highly leveraged companies, structural capital negatively affects financial performance, and RC has a positive impact. These impacts are not significant for low leveraged companies. This paper provides some new insights for managers who seek new ways to improve firm performance in the process of digital transformation.